Technology In Islamic Perspective - Ariyanto, Slamet; Basiroh, Basiroh (Jurnal Hadratul Madaniyah, 2025)
This literature study examines the lack of awareness of Muslim society towards the importance of technology using a qualitative literature study approach and documentation techniques. The results of the study identify several current technologies that can change the world, such as AI, IoT, sustainable energy, and medical innovation, and highlight the contributions of prominent Muslim scientists such as Al-Zahrawi in surgery, Al-Khawarizmi in algebra, Ibn Al-Haitam in optics, Ibn Sina in medicine, and Ibn Firnas in aviation. This study also shows Islam's support for the development of science and technology as stated in the Qur'an (Al-'Alaq 1-5, Al-Mujadilah 11, Al-Anbiya 80) and the hadith of the Prophet Muhammad SAW which emphasizes the priority of seeking knowledge and the position of knowledgeable people. Primary research data comes from the journal "Muslim Intellectual Contribution to the Development of Science and Technology" by Holis et al. (2024), Tafsir Al-Qur'an Shahih Ibnu Katsir (2017), and the article "7 Types of Technology" from Telkom University Surabaya, with the main objective of finding out the types of future technology, identifying the role of Muslim scientists in the development of science and technology, and studying the verses of the Qur'an and Hadith related to science and technology. Keywords: Technology; Islamic Perspective